Leveraging Fintech to enhance Waqf management under the State Religious Council (SIRC) in Malaysia - Mohamad, Nor Asiah (ONIKILEVHA, 2019)
The objective of this paper is to analyse the various opportunities and challenges in the synergy of Waqf management and the various financial technologies to promote and support management of Waqf. The paper sets out the existing legal and organisational framework for Waqf management at the State Islamic Religious Councils that plays the role as the institutional waqf manager in Malaysia. It shares some common criticisms or deficiencies pertaining to the management of Waqf in Malaysia. The paper also assesses the possible ways and avenues to improve the state of affairs and proposes for the employment of the various technological advancement to improve the management. The findings show among others, that the existing legal and administrative framework contributes to other issues such as lack of standardisation of policies, lack of competent manpower, lack of funds and these have brought about lack of transparency and difficulty in gaining trust from the public. The paper concludes by highlighting some possible challenges and recommendations including the use of fintech, including blockchain, as future tools to enhance Waqf management and to build trust among the public.